Censorial Interferences in the Dubbing of Foreign Films in Fascist Italy: 1927-1943 - Mereu, Carla (Meta, 2012)
Drawing insights from the project of Italia Taglia and its study on visual censorship and screening certifications in Italy, this contribution sets out to explore the censorial interferences in the Italian dubbed versions of foreign films that were publicly screened during Fascism. This study looks at practices behind the exclusion of verbal text in the target versions and highlights the rewriting of translated dialogues which contained uncomfortable political, moral and religious references. It will account for the influence of the film censorship commissions over the dubbing studios and show how the censors interfered with the process of translation, adjusting or negotiating the contents of the Italian dubbed versions.